Feedback : Top female scientists. (21st March 2016) - Young, Karl; AD, AD; Kaleberg, Kaleberg
Abstract: In response to the physicsworld.com blog post "Who is your favourite female scientist?" marking the International Day of Women and Girls in Science (10 February, http://ow.ly/YnuHa).